Studies On The Properties Of Pultruded Kenaf Fiber Reinforced Unsaturated Polyester Composites - Nosbi, Norlin (2010)
Kenaf fiber reinforced unsaturated polyester composites (KFRPC) consisting of kenaf fiber (KF) and unsaturated polyester were produced by pultrusion machine, molded into rod specimens. KF and unsaturated polyester was being analyzed and characterized in terms of degradation, physical and mechanical properties, such as immersion, strength, elongation, absorbency and surface characteristic. In this research, KF and unsaturated polyester were immersed in distilled water (DW), seawater (SW) and acidic solution (AS) at room temperature to study the behavior of the specimen after long term immersion. KF immersed in SW exhibited the highest level of water absorption, whereas KF immersed in AS showed the lowest water absorption values. The tensile strength of the immersed KF decreased with increasing immersion time implying the degradation of the fiber. Investigation on the microstructure of immersed kenaf fibers using SEM reveal the degradation of the KF with presence of microcracks and increased in the surface roughness. Effect of water immersion on the bending behavior of the unsaturated polyester was also experimentally investigated. Water diffusion was observed more in DW than SW and AS, respectively. The unsaturated polyester experienced significant reduction of the flexural strength. These are attributed to the function of the water molecules absorbed in the unsaturated polyester. KFRPC were successfully produced with 50%, 60% and 70% of KF by volume, using pultrusion method. The various percent of KF volume were tested to identify the influence of KF volume (%) on the mechanical properties.